Menginternalisasi Pendidikan Karakter Ala Ibnu Khaldun untuk Generasi Z - Azkiyah, Naila; Sitti Hawa; Herlini Puspika Sari (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to examine Ibn Khaldun’s concept of character education and its relevance in shaping the personality of Generation Z in the digital era. The background of this research stems from the growing moral and social challenges faced by young people due to rapid technological advancement and the influence of globalization. This research employs a qualitative method using a library research approach by analyzing Ibn Khaldun’s works and related literature on Islamic character education. The findings reveal that Ibn Khaldun’s perspective on character education emphasizes the balance between ‘ilm (knowledge), adab (morality and ethics), and ‘ashabiyyah (social solidarity) as the foundation for forming a civilized individual. These values are highly relevant to be applied in modern education through teacher role modeling, habituation of positive behavior, and the integration of moral values into the curriculum. The implication of this study highlights that internalizing Ibn Khaldun’s principles of character education can serve as an effective strategy to develop a knowledgeable, ethical, and resilient generation capable of facing contemporary challenges.